The bulletproof diet : lose up to a pound a day, reclaim your energy and focus, and upgrade your life - Asprey, Dave (Rodale, 2014)
"In his midtwenties, Dave Asprey was a successful Silicon Valley multimillionaire. He also weighed 300 pounds, despite the fact that he was doing what doctors recommended: eating 1,800 calories a day and working out 90 minutes a day, six times a week. When his excess fat started causing brain fog and food cravings sapped his energy and willpower, Asprey turned to the same hacking techniques that made his fortune to "hack" his own biology, investing more than $300,000 and 15 years to uncover what was hindering his energy, performance, appearance, and happiness. From private brain EEG facilities to remote monasteries in Tibet, through radioactive brain scans, blood chemistry work, nervous system testing, and more, he explored traditional and alternative technologies to reach his physical and mental prime. The result? The Bulletproof Diet, an anti-inflammatory program for hunger-free, rapid weight loss and peak performance."--